Results of Surgical Treatment of Congenital Hydronephrosis in Children - Yusupov Shukhrat Abdurasulovich; Kiyamov Azizbek Utkirovich; Kodirova Ziyodakhon Avazbek kizi (International Journal of Scientific Trends, 2025)
Congenital hydronephrosis is one of the most common urologic pathologies of childhood, accounting, according to various authors, from 2.8 to 3.5% of all congenital malformations. Thanks to the widespread introduction of prenatal ultrasound diagnostics, the frequency of detection of this pathology has increased significantly, which makes it possible to start treatment earlier and prevent the development of severe complications.